Ebla and Beyond: ancient Near Eastern studies after fifty years of discoveries at Tell Mardikh : proceedings of the international congress held in Rome, 15th-17th December 2014 - Matthiae, Paolo; Pinnock, Frances; D'Andrea, Marta (Harrassowitz Verlag, 2018)
Excavations at Ebla started in 1964. In 2014, fifty years later, an international congress was organized to try and highlight the contribution of this excavation to the knowledge of the history, philology and art history of the Ancient Near East. This book collects the papers from this international congress. Bringing together established and junior scholars from various areas, Ebla and Beyond aims at fostering the dialogue between experts in different fields of the history and archaeology of Syria in the Bronze and Iron Ages and between experienced foreign scholars and the latest generation of scholars of the School of Oriental Archaeology of Rome. The contributions in the book on the one hand show how much the discoveries at Ebla during forty-seven years of fieldwork have changed the way of understanding the developmental trajectory of Syria from the third through the first millennium BC. On the other hand, the work of the scholars from Rome and elsewhere proves how, even in difficult times for field archaeology, it is possible to exploit the results of a long-standing enterprise of this kind in a fruitful and sometimes revolutionary way